Mechanistic role of the CREB-regulated transcription coactivator 1 in cardiac hypertrophy. (February 2019) - Morhenn, Karoline; Quentin, Thomas; Wichmann, Helen; Steinmetz, Michael; Prondzynski, Maksymilian; Söhren, Klaus-Dieter; Christ, Torsten; Geertz, Birgit; Schröder, Sabine; Schöndube, Friedrich A.; Hasenfuss, Gerd; Schlossarek, Saskia; et al.
Abstract: The sympathetic nervous system is the main stimulator of cardiac function. While acute activation of the β-adrenoceptors exerts positive inotropic and lusitropic effects by increasing cAMP and Ca 2+, chronically enhanced sympathetic tone with changed β-adrenergic signaling leads to alterations of gene expression and remodeling. The CREB-regulated transcription coactivator 1 (CRTC1) is activated by cAMP and Ca 2+ . In the present study, the regulation of CRTC1 in cardiomyocytes and its effect on cardiac function and growth was investigated. In cardiomyocytes, isoprenaline induced dephosphorylation, and thus activation of CRTC1, which was prevented by propranolol. Crtc1 -deficient mice exhibited left ventricular dysfunction, hypertrophy and enlarged cardiomyocytes. However, isoprenaline-induced contractility of isolated trabeculae or phosphorylation of cardiac troponin I, cardiac myosin-binding protein C, phospholamban, and ryanodine receptor were not altered, suggesting that cardiac dysfunction was due to the global lack of Crtc1 . The mRNA and protein levels of the Gαq GTPase activating protein regulator of G-protein signaling 2 (RGS2) were lower in hearts of Crtc1 -deficient mice. Chromatin immunoprecipitation and reporter gene assays showed stimulation of the Rgs2 promoter by CRTC1. In Crtc1 -deficient cardiomyocytes, phosphorylation of the Gαq -downstream kinase ERK was enhanced. CRTC1 content was higher in cardiac tissue from patients with aortic stenosis or hypertrophic cardiomyopathy and from two murine models mimicking these diseases. These data suggest that increased CRTC1 in maladaptive hypertrophy presents a compensatory mechanism to delay disease progression in part by enhancing Rgs2 gene transcription. Furthermore, the present study demonstrates an important role of CRTC1 in the regulation of cardiac function and growth.